Biotic and Abiotic Factors Controlling Respiration Rates of Above- and Belowground Woody Debris of Fagus crenata and Quercus crispula in Japan - Jomura, Mayuko; Akashi, Yuhei; Itoh, Hiromu; Yuki, Risa; Sakai, Yoshimi; Maruyama, Yutaka (PLOS ONE, 2015)
As a large, long-term pool and source of carbon and nutrients, woody litter is an important component of forest ecosystems. The objective of this study was to estimate the effect of the factors that regulate the rate of decomposition of coarse and fine woody debris (CFWD) of dominant tree species in a cool-temperate forest in Japan. Respiration rates of dead stems, branches, and coarse and fine roots of Fagus crenata and Quercus crispula felled 4 years prior obtained in situ ranged from 20.9 to 500.1 mg CO2 [kg dry wood]–1 h–1 in a one-time measurement in summer. Respiration rate had a significant negative relationship with diameter; in particular, that of a sample of Q. crispula with a diameter of >15 cm and substantial heartwood was low. It also had a significant positive relationship with moisture content. The explanatory variables diameter, [N], wood density, and moisture content were interrelated. The most parsimonious path model showed 14 significant correlations among 8 factors and respiration. Diameter and [C] had large negative direct effects on CFWD respiration rate, and moisture content and species had medium positive direct effects. [N] and temperature did not have direct or indirect effects, and position and wood density had indirect effects. The model revealed some interrelationships between controlling factors. We discussed the influence of the direct effects of explanatory variables and the influence especially of species and position. We speculate that the small R2 value of the most parsimonious model was probably due to the omission of microbial biomass and activity. These direct and indirect effects and interrelationships between explanatory variables could be used to develop a process-based CFWD decomposition model.